In vivo and in situ programming of tumor immunity by combining oncolytics and PD-1 immune checkpoint blockade - Eric Bartee (Experimental Hematology & Oncology, 2017)
Abstract Blockade of the programmed cell death protein 1 (PD1) pathway is clinically effective against human cancers. Although multiple types of malignancies have been shown to respond to PD1 agents, only a small percentage of patients typically benefit from this treatment. In addition, PD1 therapy often causes serious immune-related adverse events. A recent study demonstrated that local, intra-tumoral, administration of modified oncolytic myxoma virus which expresses a truncated version of the PD1 protein resulted in both increased efficacy and reduced toxicity in a clinically relevant melanoma model.